Study effect of methanolic extract of Peganum Harmala and Harmine on Kidney tissue damage of diabetes mellitus in male Wistar rats - Forough Kajbaf; Shahrbanoo Oryan; Ramesh Ahmadi; Akram Eidi (بیولوژی کاربردی, 2020)
Introduction: The dangerous side effects of diabetes are diabetic nephropathy, which has a relatively high prevalence in diabetic patients and causes renal failure. Investigating the process of destruction and the mechanisms that prevent it, in order to reduce the tissue damage, especially with the treatment of plants, can be a significant issue. Material and methods: In this research, Espand with scientific name of Peganum harmala, a plant of the Zygophyllaceae family and its effective substance called harmine in diabetes-induced renal injury, were studied on 80 male Wistar rats in experimental and diabetic groups. Rats were treated with methanolic extract of seeds and leaves of Peganum Harmala and Harmine. After tissue passage and fixation, Microscopic slides were prepared and studied. In tissue studies, four factors of epithelial changes, tubular destruction, leukocyte inflammation and capillary obstruction were detected in the kidneys. Results: The diabetic rat group received harmine and the diabetic rats receiving the extract of the seed were less damaged, while in the diabetic rats recieveing the leaf extract these lesions was higher and it was interesting to note that there was no difference in the experimental groups with the positive control group. Conclusion: According to the tissue results in our study, seed extract and harmine have the ability to prevent tissue damage caused by diabetes, which can be attributed to the harmine alkaloid in the seed.